Adapting a Residential Course to Web-Based Blended Learning - Ozmen, Busra; Tepe, Tansel; Tuzun, Hakan (Ani Yayincilik, 2018)
Purpose: This study describes the design of the Basic English 1 and Basic English 2 courses taught in the Foreign Languages School (FLS) of a large public university in Turkey as blended learning in a mostly distance education system. Research Method: This study was structured as a case study describing an instructional design effort. The study used the ADDIE instructional design model to convert these courses into the distance education format. In the analysis phase, the designers held discussions with the FLS lecturers to determine their needs and contextual limitations. These discussions revealed the knowledge and skills of the FLS students, the expectations of the lecturers and students, and the course objectives. The design process focused on determining Basic English 1 and 2 learning activities and presentation formats for these activities. Each course has a duration of 15 weeks and includes the skills of grammar, reading comprehension, writing, listening comprehension, and speaking. In the development phase, the designers added all the tools from the design phase to the Moodle environment. In the implementation phase, the designers conducted usability tests with the students and identified deficiencies of the design phase. In the evaluation phase, the designers improved the content based on student feedback from the usability tests. Findings: The designers conducted a planned and systematic design process based on the ADDIE instructional design model. At the end of the design process, the course content was transferred to the Moodle environment, and a usability test was administered to the students. The designers revised the environment's design based on student feedback. Eventually, the study presented an environment that was suitable for blended learning educational activities that mainly used distance education. Implications for Research and Practice: Designing blended learning opportunities for formal learning environments is a rising trend, and the community can benefit from the documented design process. (C) 2018 Ani Publishing Ltd. All rights reserved
Yüz yüze verilen bir dersin web tabanli karma Ögrenmeye uyarlanmasi
Keywords: ADDIE instructional design model; distance education; foreign language learning; instructional design; learning management systems